Leaf spot of Hosta ventricosa caused by Fusarium oxysporum in China - Wang, Chunxia; Zhang, Hulei; Wang, Shenhai; Mao, Shengfeng (PeerJ, 2021)
Leaf spot of Hosta ventricosa is a new disease in China. This disease seriously affects the ornamental value and greening function of H. ventricosa. Identification of the causal agent can prevent and control leaf spot in H. ventricosa and promote the healthy development of the H. ventricosa industry. Known incidents of leaf spot of H. ventricosa occurred in three places, and samples were collected. After the fungus were isolated, its pathogenicity was tested according to Koch’s postulates. Isolates ZE-1b and ZE-2b were identified as Fusarium oxysporum based on morphological features and multigene phylogenetic analyses of calmodulin (CMDA), RNA polymerase II subunit A (RPB1), RNA polymerase II second largest subunit (RPB2) and translation elongation factor 1-alpha (TEF1). These results provide a theoretical basis for the control of this disease of H. ventricosa.
Keywords: Fungi; Hosta ventricosa; Fusarium oxysporum; Multi gene phylogeny; New disease